Transcontinental patterns in floral pigment frequencies among animal-pollinated species - Narbona, Eduardo; Del Valle, Jose C.; Whittall, Justen B.; León-Osper, Melissa; Buide, M. Luisa; Pulgar, Iñigo; Camargo, Maria Gabriela Gutierrez [UNESP]; Morellato, Leonor Patricia Cerdeira [UNESP]; Rodríguez-Castañeda, Nancy; Rossi, Victor; Conrad, Katie; Hernandez-Mena, Joey; et al. (Cold Spring Harbor Laboratory, 2024)
Abstract Flower coloration arises primarily from pigments that serve dual functions: attracting pollinators and mitigating environmental stresses. Among major flower pigment groups, anthocyanins and UV-absorbing phenylpropanoids are particularly notable for fulfilling both roles. Their importance suggests that both pigment types should be widespread in flowers. Here, we analyze the UV-Vis absorption profiles of major floral pigments to assess their potential protective role against UV radiation and demonstrate that this protection is largely confined to UV-absorbing phenylpropanoids. We also analyzed the floral pigment composition of 926 animal-pollinated species from California, southern Spain, and southeastern Brazil. UV-absorbing phenylpropanoids were ubiquitous, while anthocyanins occurred in ∼56% of species, carotenoids in ∼37%, and chlorophylls in ∼17%. Pigment frequencies varied with abiotic and biotic factors, such as light environment in Spain, and pollinator type, such as insect versus hummingbird, in California. Despite these local differences, our findings reveal a consistent regional distribution of floral pigments.